A RANDOMIZED CLINICAL TRIAL ON THE ROLE OF THORACIC SPINE MANIPULATION AND SCAPULAR STABILIZATION IN SUBACROMIAL SHOULDER IMPINGEMENT SYNDROME - Kumar, Manas; Jain, Dr. Annu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Subacromial shoulder impingement syndrome (SSIS) is a common cause of shoulder pain that significantly impacts functional ability and quality of life. This randomized clinical trial examined the effectiveness of thoracic spine manipulation (TSM) combined with scapular stabilization exercises (SSE) compared to standard physical therapy for patients with SSIS. One hundred and twenty participants with diagnosed SSIS were randomly assigned to either an experimental group (TSM+SSE) or a control group (standard care). Outcomes were measured using the Shoulder Pain and Disability Index (SPADI), pain visual analog scale (VAS), range of motion (ROM), and patient-reported functional outcomes at baseline, 4 weeks, and 8 weeks. Results demonstrated that the TSM+SSE group showed significantly greater improvements in pain reduction (mean difference 2.1 points on VAS, p<0.001), shoulder function (mean difference 14.3 points on SPADI, p<0.001), and ROM (mean increase of 23° in scapular upward rotation, p<0.001) compared to the control group at 8 weeks. These findings suggest that the integration of thoracic spine manipulation with targeted scapular stabilization exercises provides superior outcomes for SSIS management compared to standard care alone, supporting a regional interdependence approach to rehabilitation.